The complete chloroplast genome sequence of Fagraea fragrans - Jinfeng Zhang; Yunqing Li; Yi Wang (Mitochondrial DNA. Part B. Resources, 2020)
The first complete chloroplast genome (cpDNA) sequence of Fagraea fragrans was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 154,416 bp in length, contains a large single copy region (LSC) of 84,405 bp and a small single copy region (SSC) of 18,285 bp, which were separated by a pair of inverted repeats (IR) regions of 25,863 bp. The genome contains 130 genes, including 85 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. The overall GC content of the whole genome is 38.0%, and the corresponding values of the LSC, SSC, and IR regions are 36.0%, 31.8%, and 43.4%, respectively. Further phylogenomic analysis showed that F. fragrans in a unique clade in Gentianaceae family.